A novel design of flag sequences for low-complexity delay-doppler estimation - Meng, Lingsheng (2023)
This paper presents a novel design of Flag sequences whose ambiguity functions (AFs) are featured by the peak-curtain property. Such a property can be exploited for efficient identification of the AF peak by first searching the curtain, thus leading to low-complexity delay-Doppler estimation. Motivated by the high AF sidelobes of the existing Flag sequences, we propose to minimize the customized weighted integrated sidelobe level (CWISL) with the aid of an Accelerated Partially Majorization-Minimization Algorithm (APMMA). Numerical results demon-strate that our optimized Flag sequences have lower CWISL and peak sidelobe level (PSL) in the delay-Doppler zone of interest.